Isoprenoid addition to Ras protein is the critical modification for its membrane association and transforming activity. - Kato, K (1992)
We have introduced a variety of amino acid substitutions into carboxyl-terminal CA1A2X sequence (C = cysteine; A = aliphatic; X = any amino acid) of the oncogenic [Val12]Ki-Ras4B protein to identify the amino acids that permit Ras processing (isoprenylation, proteolysis, and carboxyl methylation), membrane association, and transformation in cultured mammalian cells. While all substitutions were tolerated at the A1 position, substitutions at A2 and X reduced transforming activity. The A2 residue was important for both isoprenylation and AAX proteolysis, whereas the X residue dictated the extent and specificity of isoprenoid modification only. Differences were observed between Ras processing in living cells and farnesylation efficiency in a cell-free system. Finally, one farnesylated mutant did not undergo either proteolysis or carboxyl methylation but still displayed efficient membrane association (approximately 50%) and transforming activity, indicating that farnesylation alone can support Ras transforming activity. Since both farnesylation and carboxyl methylation are critical for yeast a-factor biological activity, the three CAAX-signaled modifications may have different contributions to the function of different CAAX-containing proteins.